(3oZQQ GdNUGFU GdhGVMI hoYQQ GdfbGFU GdaGVMIs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW,J (B718 (3g` s ((3YHOGdMb Hf YHOGdhgGH GdefGYej GdYhaj s)
(3ChdgG (B:s
(3hHYO aEfj deG QCjJ JZGjQ eYGfj GdCNdGb, OGdkG Ydi JHGjf eHGfj GdCYQGb s
(3BNQgG (B:s
(3Efg ef QGLjg bQjH, hdOGYjg SejY eLjH bO GfJgi gPG GdcJGH GdYLjH s
(3HgG fXGe GdJYbjHIs
(3fUaGfs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B143s
Keywords: (3GdCOHs